Fuel Consumption, Emissions of Air Pollutants and Opportunities for Reducing CO2 Emissions from Linear Sources in the Model Rural Municipality - Anita Konieczna; Kamil Roman; Witold Rzodkiewicz (Energies, 2023)
The study estimates the amount of emissions resulting from linear sources. There were calculations for a model rural municipality, composed of national, provincial, country, and municipal roads that run through the area. In this study, the following categories of vehicles were assumed to travel along this route: motorcycles, passenger cars, light trucks (vans), heavy trucks without trailers, trucks with trailers, and buses. The analysis used data on the average volume of traffic (SDR) on selected roads on the territory of the sample municipality, based on the frequency of participation in traffic by each mode of transportation on selected road sections. To estimate the emission rates of each pollutant, for each vehicle category separately, the calculations were made based on the emission factor rates for each type of fuel. According to the adopted methodology and based on the adopted assumptions scenarios, pollutants’ emissions were estimated. The implementation of the scenarios offered for reducing CO2 emissions has been proposed, and it is estimated that, depending on the variant adopted, the reductions will be between 13 and 21% in variant I, between 3 and 8% in variant II, and between 18 and 34% in combining these variants. The variant with a reduction in private car transportation in favor of bicycle transportation in combination with public transportation showed the most favorable effects on the environment.